PENGARUH LENGAS TANAH TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS LOKAL BAWANG MERAH PADA KETINGGIAN TEMPAT BERBEDA - Muhammad Anshar; Tohari Tohari; Bambang Hendro Sunaminto; Endang Sulistyaningsih (Universitas Tadulako, 2011)
Pot experimental research under green house condition was carried out in Yogyakarta during March-Mei 2009. The aim of the experiment was to determine the influence of soil moisture on growth and yield of local-varieties shallots (Palasa, Palu and Sumenep) at different elevations. The experiment was arranged in a Split Split Plot Design with three replications. The main plot was local varieties of shallot: (1) Palasa; (2) Palu; and (3) Sumenep. The sub-plot were soil moisture (field capacity percentage - % FC), included: (1) 50% FC; (2) 100% FC; and (3) 150% FC. Each variety has a different response to different soil moisture and altitude places. Sumenep variety had the lowest net assimilation rate (NAR) and Palasa variety produced smallest fresh-bulb at all soil moisture and elevation. Soil moisture at 100% FC increased crop growth rate (CGR) and bulb’s fresh-weight per crop bunch of Palu variety particularly on elevation 100 m above sea level, whereas 50% FC reduced shallot growth and yield on all elevation.